CONSIDERAÇÕES SOBRE O PROCESSO ENSINO-APRENDIZAGEM DE FUNÇÕES - Leite, Luciano Roque (2016)
This work has as main purpose to present a pedagogical proposal for teaching of functions in High School. To this end, it was carried out a literature research seeking for works that proved that the proposed objective can be achieved, relating the different representations in various teaching methodologies, emphasizing how the concept is introduced. At first, it was presented the difficulties in the teaching-learning process of functions and discussed their different representations, high lighting the importance of technology information in this process. The content of functions was chosen because it is an important issue of basic education and the students demonstrated great difficulties. Therefore an overview of the history of functions took place, definition, and activities involving linear function and quadratic function using GeoGebra software, inverse function and composite function. It was proposed a number of activities, such as calculating machine, identification of regularities and graphs of functions with Google support which may be used in the classroom. It was discussed about the teacher’s responsibility by teaching this content using computers in school.